Performance efficiency comparison of microbial electrolysis cells for sustainable production of biohydrogen—A comprehensive review. (5th January 2022) - Muddasar, Muhammad; Liaquat, Rabia; Aslam, Ayesha; Ur Rahman, Muhammad Zia; Abdullah, Ali; Khoja, Asif Hussain; Latif, Kainaat; Bahadar, Ali
Summary: Microbial electrolysis cells (MECs) are one of the most promising innovation amongst bio‐electrochemical systems for biohydrogen production. A wide variety of wastewaters and organic wastes that is, sodium acetate, glucose, glycerol, domestic wastewater, sugar industries effluent, food processing wastewater, industrial wastewater, etc. can be utilized as substrates in MEC. The objective of this comprehensive review is to study the effects of reactor configuration, electrode materials, and substrates on the maximum hydrogen production rate (HPR) and columbic efficiency (CE) of the MEC system. The obtained results were summarized based on reactor configuration, substrate concentration, electrodes, applied voltage, HPR, and CE. Despite this significant progress, MEC technology still requires substantial developments to be recognized as a commercially viable technology. At the end of this review, the most promising future perspectives were also discussed which could be the appealing solutions for various problems associated with MEC technology. This review supports energy engineers and researchers to analyze the performance of various MECs for future assistance in research.